The role of plant parasitic nematodes on productivity reduction of banana and tomato in East Kalimantan, Indonesia - SUYADI, SUYADI; ROSFIANSYAH, ROSFIANSYAH (Asian Journal of Agriculture, 2017)
Suyadi, Rosfiansyah. 2017. The role of plant parasitic nematodes on productivity reduction of banana and tomato in East Kalimantan, Indonesia. Asian J Agric 1: xxxx. Plant parasitic nematode is one of the most limiting factor of agricultural ecosystem productivity in East Kalimantan, but their occurrence in agricultural field as a cropâ€™s pest generally undistinguished, due to their microscopic size and their existence wrapped in the roots or soil particles. However, plant parasitic nematodes might cause yield loss up to 75%, without showed any disease symptom on crop morphologically. Perennial crop and annual crop under intensive cultivation usually experience high yield loss due to plant parasitic nematodes, if crop protection management was not implemented properly. This research aimed to determine the role of plant parasitic nematodes in reducing cropâ€™s productivity in East Kalimantan, in relation to agricultural practices implemented by farmers. A descriptive research and comparative analyses were implemented to determine the role of plant parasitic nematode on yield reduction of banana and tomato as the indicator of productivity. Based on the field observation related to pest management in East Kalimantan, it was determined that plant parasitic nematode existence was neglected by farmers and no significant effort was implemented to control plant parasitic nematodes population. Therefore, low productivity of agricultural ecosystem in East Kalimantan was reported by Statistical Office, and it was not only caused by soil fertility problems, in some crops it was also the impact of population outbreak of plant parasitic nematodes. The first ranking three genera of plant parasite nematodes observed in East Kalimantan were Meloidogyne, Radhopholus, and Rotylenchulus, respectively. Meloidogyne and Rotylenchulus were major pest on vegetables, and caused yield loss >50% on tomato. While, genus of Radhopholus was the major pest on banana, and caused yield loss >75% on banana.